1987
DOI: 10.1038/328395a0
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics of an antigen required for its interaction with Ia and recognition by T cells

Abstract: A detailed analysis of the residues within an immunogenic peptide that endow it with the capacity to interact with Ia and to be recognized by T cells is presented. Ia interacts with only a few of the peptide residues and overall exhibits a very broad specificity. Some residues appear to interact both with Ia and with T cells, leading to a model in which a peptide antigen is 'sandwiched' between Ia and the T-cell receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
202
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 369 publications
(212 citation statements)
references
References 0 publications
10
202
0
Order By: Relevance
“…On the basis of statistical analysis it has been suggested that immunodominant sites in T cell stimulating peptides have a high conformational propensity [19] and several workers have proposed that the ability to form secondary structure is important for antigenicity [20][21][22][23][24][25][26]. In particular, Berzofsky and co-workers [27] have shown that 18 out of 22 known immunodominant helper T cell epitopes correspond to sequences that are predicted to form stable amphipathic helices.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of statistical analysis it has been suggested that immunodominant sites in T cell stimulating peptides have a high conformational propensity [19] and several workers have proposed that the ability to form secondary structure is important for antigenicity [20][21][22][23][24][25][26]. In particular, Berzofsky and co-workers [27] have shown that 18 out of 22 known immunodominant helper T cell epitopes correspond to sequences that are predicted to form stable amphipathic helices.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, Troybodies were constructed that have V regions specific for class II molecules, and various model T cell epitopes in the constant part. As model T cell epitopes, the following were used: aa residues 91-101 from the mouse 2 315 Ig L chain (33), 323-339 OVA (27), 110 -120 HA (25), and 46 -61 HEL (26). The 2 315 epitope is presented on I-E d class II molecules to CD4 ϩ T cells (6,33), as is the HA epitope (36).…”
Section: Construction Of Mhc Class Ii-specific Troybodies With T Cellmentioning
confidence: 99%
“…Also, the association pattern of peptides to different allele variants of murine Ia is a reflection of the MHC restriction of the immune response [3,4]. Several workers have attempted to unravel the relevant struc-tural requirements of TD h peptides to interact with murine [5][6][7] or human [8 -14] class II molecules. The X-ray structure of a class II molecule [15] has confirmed that the groove is occupied by a single peptide, and also, that its structure is similar to the one found for class I molecules [16].…”
Section: Determinants Recognized By T-helper Cellsmentioning
confidence: 99%